PREDICTING PHYSICAL AND MECHANICAL PROPERTIES OF SPECIAL FABRICS - Murodkhujaeva , K.B.; Sodikova , N.R (Educational Research in Universal Sciences, 2023)
This article analyzes the production technology of special fabrics, the composition of fabrics and their physical and mechanical properties.